Formation of Competencies of Humanitarian Direction in the Process of Professional Preparation of the Future Specialists in the Sphere of Law - Denyshchyk, Oleksii (Pedagogical Discourse, 2015)
The article deals with the theoretical grounds of preparation of the future professionals in the sphere of law according to the Law of Ukraine «About Higher Education» (2014), which determined as one of the prior directions of educational policy in the modern period of time transition from the knowledge paradigm to the competence approach. On the basis of the analysis of more than 100 sources written by psychologists, pedagogues, lawyers, sociologists, managers and other domestic and foreign scientists the genesis of the notions «competency», «competence», «competences», «professional competence» has been studied. When studying competence approach as the system making factor, it is accentuated that reforming of Ukraine’s educational system is possible on the basis of further humanitarization of students’ knowledge, consolidation of the principle of student-centrism and offering real autonomy to each higher educational establishment and freedom to each pedagogical worker. Taking into account the scientists’ ideas in the sphere of law in the structure of competence of the future specialists 4 aspects can be singled out: gnoseological, normative, functional and personal. Own vision of competences of humanitarian block is offered: ways of thinking, professional, world outlook and civil qualities, and moral-ethic values, abilities and skills, necessary for lawters-professionals. Pedagogical conditions of forming harmonically-developed personality of a professional of the XXI century have been determined.